2019
DOI: 10.1007/s00238-019-01615-w
|View full text |Cite
|
Sign up to set email alerts
|

The effect of microsurgical training on novice medical students’ basic surgical skills—a randomized controlled trial

Abstract: Background It has been demonstrated that medical students are capable of learning microsurgical techniques. We hypothesize that microsurgical training might give insight into the importance of delicate tissue handling and correct knot tying that could have a positive influence on macrosurgical skills. The primary aim of this study was to evaluate the effect of microsurgical training on macrosurgical suturing skills in novice medical students. Subjects and methods In 2018, 46 novice medical students were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Naturally, as medical students progress through their clerkship in the medical school, their knowledge and perceptions regarding medical and surgical specialties should increase due to university-based instructions. 33 Studies comparing pre-clinical years 9 , 21 and clinical years, 12 , 16 , 17 , 23 found media to be a primary source of information. Ultimately, the lack of foundational knowledge in plastic surgery adversely impacted students who gravitate towards a career in plastic surgery and hindered their progression in this competitive field.…”
Section: Discussionmentioning
confidence: 99%
“…Naturally, as medical students progress through their clerkship in the medical school, their knowledge and perceptions regarding medical and surgical specialties should increase due to university-based instructions. 33 Studies comparing pre-clinical years 9 , 21 and clinical years, 12 , 16 , 17 , 23 found media to be a primary source of information. Ultimately, the lack of foundational knowledge in plastic surgery adversely impacted students who gravitate towards a career in plastic surgery and hindered their progression in this competitive field.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no baseline test (pre-test) was performed, and skills were assessed only using a macrosurgical skill task for each group. A microsurgical task was conducted in the experimental group, but the scores were not compared to those of the control group as they did not perform the microsurgical task [25]. With 38 surgical residents (PGY1-3), this randomized controlled trial compared four surgical training sessions using a Penrose drain, a synthetic artery model, and turkey arteries either compressed in one day or spread across four weeks [14,26].…”
Section: Previous Microsurgery Education Trialsmentioning
confidence: 99%
“…Different objective assessments tools and scoring systems to determine the quality of the training provided to trainees. International consensuses on minimum standards for microsurgical courses [19,20], minimum microsurgery case requirements [21] and several validated training models with objective structured assessment of technical skills (OSATS) have been devised to evaluate the trainers' performance in microsurgery [22][23][24][25].…”
Section: Objective Assessment Tools For Microsurgical Trainingmentioning
confidence: 99%